Integration of Social Science Learning Through A Child-Friendly Ethnoscience Approach - Yuliyanti, Novi; Sarwi, Sarwi; Wardani, Sri; Fathonah, Siti (Proceedings of International Conference on Science, Education, and Technology, 2024)
Child-friendly education in elementary schools is not just about transferring knowledge or content. The rapid development of science and technological advances will have major consequences. Not only are the needs of society changing, but it also becomes a vehicle for internalizing character that originates from the values and culture of society. This concept gives rise to logical consequences, namely that every learning process, whatever the topic, must integrate cultural values as character education content, including social studies and science learning. One of the cultural elements that can be integrated in social studies and science learning is ethnoscience (indigenous public science) which is child-friendly for elementary school students. Ethnoscience is an original science (a community's knowledge system). Analysis of the literature shows that the integration of the ethnoscience approach can help the process of learning social science for students in elementary schools by paying attention to their special needs, facilitating the development of critical thinking and problem-solving skills, and enriching the learning experience through the integration of local, traditional, and contextual knowledge. However, the challenges in integrating this approach, such as a deep understanding of students' cultural diversity and the development of relevant curricula, also need to be considered. Taking these findings into account, further research can develop strategies and best practices in implementing an ethnoscience approach in science learning in elementary schools, creating a meaningful learning environment for all students.